2017
DOI: 10.1002/zaac.201600423
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive SPHYB and B3LYP-DFT Studies of Two Types of Ferrocene

Abstract: Structural and optoelectronic properties of ferrocene (FeC10H10) using various exchange correlation potentials including Spin Polarized Generalized Gradient Approximation (SPGGA), Hybrid Density Functional Theory (SPHYB‐DFT), and hybrid density functional Becke3LYP are investigated. Obtained bandgap by the SPHYB‐DFT and SPGGA methods show consistency with the experiment, that are indirect and direct, respectively. The cell size effects on physical properties of ferrocene studied about two types of its lattice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 56 publications
(72 reference statements)
3
4
0
Order By: Relevance
“…For Fc complexes, the HOMO is concentrated only on the ferrocenyl moiety while the LUMO is more equally distributed in the whole molecule. This is in agreement with previous calculations. ,, ESP maps show that the most negative part is located mostly on the CO bond for all compounds, while the most positive part is found on the O–H sites. In case of Fc complexes, the positive charges are also found on the ferrocenyl moieties.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…For Fc complexes, the HOMO is concentrated only on the ferrocenyl moiety while the LUMO is more equally distributed in the whole molecule. This is in agreement with previous calculations. ,, ESP maps show that the most negative part is located mostly on the CO bond for all compounds, while the most positive part is found on the O–H sites. In case of Fc complexes, the positive charges are also found on the ferrocenyl moieties.…”
Section: Resultssupporting
confidence: 93%
“…In the complex structures, the ligands are similarly presented and the cyclopentadienyl rings make an angle of 86–87° versus the phenyl ring of the ligands through the dihedral C12–N–C cp –C cp . The ferrocenyl moieties are in the eclipse form with a Fe–C distance of about 2.11–2.13 Å, which is in agreement with analogous ferrocenes. , The optimized geometries, HOMO, LUMO, and ESP maps of all compounds are presented in Figure S11. Principal coordination parameters of all structures are reported in Table S1.…”
Section: Resultssupporting
confidence: 63%
See 2 more Smart Citations
“…Density functional theory gives reasonable geometries for metallocene molecules [24,25,26]. Xu et al [27] compared several gradient-corrected functionals, as well as the local density approximation (LDA), and found that the B3LYP functional gives the best agreement between the experimental and theoretical molecular geometry.…”
Section: Assessing Van Der Waals (Vdw) Functionalsmentioning
confidence: 99%